Asymmetric and Symmetric Dimethylarginine Predict Outcomes in Patients With Atrial Fibrillation: An ARISTOTLE Substudy - Horowitz, John D; De Caterina, Raffaele; Heresztyn, Tamila; Alexander, John H; Andersson, Ulrika; Lopes, Renato D; Steg, Philippe Gabriel; Hylek, Elaine M; Mohan, Puneet; Hanna, Michael; Jansky, Petr; Granger, Christopher B; et al. (Journal of the American College of Cardiology, 2018)
BACKGROUND: There is little mechanistic information on factors predisposing atrial fibrillation (AF) patients to thromboembolism or bleeding, but generation of nitric oxide (NO) might theoretically contribute to both. OBJECTIVES: The authors tested the hypothesis that plasma levels of the methylated arginine derivatives asymmetric and symmetric dimethylarginine (ADMA/SDMA), which inhibit NO generation, might be associated with outcomes in AF. METHODS: Plasma samples were obtained from 5,004 patients with AF at randomization to warfarin or apixaban in the ARISTOTLE (Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation) trial. ADMA and SDMA concentrations were measured by high-performance liquid chromatography. Relationships to clinical characteristics were evaluated by multivariable analyses. Associations with major outcomes, during a median of 1.9 years follow-up, were evaluated by adjusted Cox proportional hazards models. RESULTS: Both ADMA and SDMA plasma concentrations at study entry increased significantly with patients' age, female sex, renal impairment, permanent AF, or congestive heart failure. ADMA and SDMA increased (p < 0.001) with both increased CHA2DS2-VASc and HAS-BLED scores, but decreased in the presence of diabetes. On multivariable analysis adjusting for established risk factors and treatment, tertile groups of ADMA concentrations were significantly associated with stroke/systemic embolism (p = 0.034), and death (p < 0.0001), whereas tertile groups of SDMA were associated with major bleeding and death (p < 0.001 for both). Incorporating ADMA and SDMA into CHA2DS2-VASc or HAS-BLED predictive models improved C-indices for those outcomes. Neither ADMA nor SDMA predicted differential responses to warfarin or apixaban. CONCLUSIONS: In anticoagulated patients with AF, elevated ADMA levels are weakly associated with thromboembolic events, elevated SDMA levels with bleeding events and both are strongly associated with increased mortality. These findings suggest that disturbances of NO function modulate both thrombotic and hemorrhagic risk in anticoagulated patients with AF. (Apixaban for Reduction in Stroke and Other Thromboembolic Events in Atrial Fibrillation [ARISTOTLE]; NCT00412984).
Keywords: pyrazoly; Humans; lidé středního věku; warfarin; Warfarin; Double-Blind Method; Predictive Value of Tests; Pyridones; Female; Aged; výsledek terapie; senioři; dvojitá slepá metoda; lidé; Atrial Fibrillation; Biomarkers; fibrilace síní; Arginine; biologické markery; ženské pohlaví; Male; Middle Aged; prediktivní hodnota testů; Treatment Outcome; arginin; Aged, 80 and over; pyridony; senioři nad 80 let; mužské pohlaví; Pyrazoles; antikoagulancia; Anticoagulants; inhibitory faktoru Xa; Factor Xa Inhibitors